The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1198/016214508000000508
|View full text |Cite
|
Sign up to set email alerts
|

Binary Time Series Modeling With Application to Adhesion Frequency Experiments

Abstract: Repeated adhesion frequency assay is the only published method for measuring the kinetic rates of cell adhesion. Cell adhesion plays an important role in many physiological and pathological processes. Traditional analysis of adhesion frequency experiments assumes that the adhesion test cycles are independent Bernoulli trials. This assumption can often be violated in practice. Motivated by the analysis of repeated adhesion tests, a binary time series model incorporating random effects is developed in this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Further extensions can be made by replacing Z t (x) with a spatio-temporal Gaussian process Z(t, x), but the computational cost will be higher. Without the Gaussian process assumption in (3), the mean function is closely related to the Zeger-Qaqish (1988) model and its extensions in Hung et al (2008) and Benjamin et al (2003), all of which take into account the autoregressive predictors in logistic regression.…”
Section: Generalized Gaussian Process Models For Binary Time Seriesmentioning
confidence: 99%
“…Further extensions can be made by replacing Z t (x) with a spatio-temporal Gaussian process Z(t, x), but the computational cost will be higher. Without the Gaussian process assumption in (3), the mean function is closely related to the Zeger-Qaqish (1988) model and its extensions in Hung et al (2008) and Benjamin et al (2003), all of which take into account the autoregressive predictors in logistic regression.…”
Section: Generalized Gaussian Process Models For Binary Time Seriesmentioning
confidence: 99%
“…Moreover, the thermal fluctuations are independently distributed given their binding status (e.g., binding or not), but the transition from one status to another can be dependent. For example, in some receptor-ligand systems (Zarnitsyna et al 2007;Hung et al 2008), the chance of having a binding in the next contact is increased (or decreased) if there is a binding in the immediate past. Because of the dependence, standard approaches such as change point techniques (Bhattacharya 1994;Carlstein et al 1994;Hawkins and Zamba 2005;Krishnaiah and Miao 1988) are not directly applicable.…”
Section: Introductionmentioning
confidence: 98%
“…We consider a weight vector suggested in Zou (2006) witĥ ν j = |β j | −ρ , where ρ > 0 andβ j is a root-n-consistent estimator of β j . In Hung (2011), it is shown that the MLE of β is root-n-consistent under model (2), therefore it can be applied.…”
mentioning
confidence: 99%